Molecular cloning and characterization of p38 gene in the Chinese Mitten Crab, Eriocheir sinensis. (11th October 2014) - Zhao, Jin Cheng; Wang, Yuan Li; Li, Qing; Zhu, Ming; Sun, Wen Juan; Wu, Tian Min; Wang, Qun; He, Lin
Abstract: p38 is an important component of the MAPK signaling pathways as a Ser/Thr protein kinase. We cloned the full length p38 ( Es‐p38 ) cDNA sequence in Eriocheir Sinensis which contained a 1098‐nucleotide ORF that encoded a protein of 365 amino acids. Es‐p38 protein has a p38 MAPK functional domain (STKc_p38), it is a typical serine/threonine kinase and processes all p38 protein's conservative T‐G‐Y motif. Tissue expression of the Es‐p38 gene and expression during testis development stages were determined by quantitative real‐time PCR analysis. The results show that Es‐p38 gene is expressed in various tissues, but it expresses higher in the muscle, hepatopancreas, intestine, ovary and testis. The expression level of Es‐p38 gene at different stages of testis development shows no significant difference between the spermatocyte phase (July–August) and spermatid stage (August–October), but it rises significantly in the mid‐late period of sperm stage (December–January). This changing trend has a positive relationship with the E. Sinensis gonad development and reproduction stage, which preliminarily shows that Es‐p38 may function in the E. Sinensis testis development and the process of spermatogenesis.